2014
DOI: 10.2478/s11756-014-0486-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and purification of anticancer enzyme L-glutaminase from Alcaligenes faecalis KLU102

Abstract: L-Glutaminase, an amidohydrolase, is gaining importance on account of its potential anticancer activity. L-Glutaminase produced by Alcaligenes faecalis KLU102, isolated from the marine realm (Bay of Bengal), exhibits potential anticancer activity. Response surface methodology was employed for optimizing the medium composition. The concentrations of the various constituents were as follows: arabinose (2%), skim milk (4%), and salts viz. K2HPO4, KH2PO4, MgSO4, and NaCl (2%). The bacterium grown in the optimized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 30 publications
(30 reference statements)
0
24
0
Order By: Relevance
“…Suresh et al (2013) reported optimization of medium components through OFAT approach and FCCCD for the submerged production of L-glutaminase by Serratia marcescens. Pandian et al (2014) reported the statistical optimization of medium composition for the production of glutaminase from Alcaligenes faecalis KLU102. RSM was used for optimization and the bacterium grown in the optimized medium [arabinose (2%), skim milk (4%) and sodium chloride (2%)] yielded L-glutaminase activity of 1.34 IU/mg.…”
Section: Optimization Using Ccdmentioning
confidence: 99%
See 2 more Smart Citations
“…Suresh et al (2013) reported optimization of medium components through OFAT approach and FCCCD for the submerged production of L-glutaminase by Serratia marcescens. Pandian et al (2014) reported the statistical optimization of medium composition for the production of glutaminase from Alcaligenes faecalis KLU102. RSM was used for optimization and the bacterium grown in the optimized medium [arabinose (2%), skim milk (4%) and sodium chloride (2%)] yielded L-glutaminase activity of 1.34 IU/mg.…”
Section: Optimization Using Ccdmentioning
confidence: 99%
“…Supplementation of sucrose and yeast extract as carbon and nitrogen source improved Lglutaminase production by Zygosaccharomyces rouxii while higher L-glutaminase production was noticed in Providencia species with glucose and urea as carbon and nitrogen source, respectively. Recently, there are several reports which confirm the fact that the carbon and nitrogen sources significantly affect the production of Lglutaminase by microorganisms (Sathish and Prakasham, 2013;Krishnakumar et al, 2011;Pandian et al, 2014;Jesuraj et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The activity of glutaminase was determined by the modied Nesslerization method adopted from the literature. 7 Briey, 2800 mL reaction mixture contained 3.5 mM of glutamine solution prepared in 50 mM Tris-HCl buffer, pH 9.0. To this mixture, 100 mL (100 mg) of the enzyme was added, and the mixture was incubated for 10 min at 70 C. The reaction was terminated by the addition of 100 mL of 500 mM trichloroacetic acid aer the incubation period.…”
Section: Measurement Of the Glutaminase Activitymentioning
confidence: 99%
“…5,6 Thus, Lglutaminase is an attractive target to block the energy route for the proliferation of glutamine-dependent tumour cells and responsible for their selective death. 7,8 Several other applications of the enzyme have been reported due to its effective antiretroviral activity; 9 moreover, the enzyme is used to improve the taste and aroma of the food products. 10 L-Glutaminase also has a signicant application in biosensors where it is used to monitor the level of glutamine in mammalian and hybridoma cells.…”
Section: Introductionmentioning
confidence: 99%